Iron-Enriched Dim Sum with Moringa and Tempeh Flour: A Dietary Approach to Preventing Anemia in Pregnant Women - Yeni Rusli; Arif Sabta Aji; Veriani Aprilia; Siska Ariftiyana (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2025)
Anemia in pregnant women is a public health problem with a high prevalence in Indonesia, one of the main causes of which is low iron intake. This study aimed to analyze the iron content of dim sum formulated with moringa leaf and tempeh flour substitution as a food product to prevent anemia in pregnant women. This was an experimental study with a completely randomized design (CRD) consisting of a single factor and three ratio variations of moringa leaf to tempeh flours such as F0 (control, without substitution), F1 (ratio 1:2), F2 (ratio 1:1), and F3 (ratio 2:1). The iron content was analyzed using the visible spectrophotometer. The results showed significant differences in iron content among the treatments (p ≤ 0.001). F0, F1, F2, and F3 had an iron content of 2.54±0.21; 3.37±0.37; 3.81±0.06; and 4.63±0.26 mg 100 g-1, respectively. The F3 treatment had the highest iron content and significantly differed from the F0 control formula. Based on the results, moringa leaf flour contains iron, which plays a role in hemoglobin formation. At the same time, tempeh, rich in protein, helps support the production of red blood cells and prevents anemia. This modified dim sum can potentially be a source of iron-rich food that can help prevent anemia, especially in pregnant women.